Effects of dietary proline on swim bladder collagen synthesis and its possible regulation by the TGF‐β/Smad pathway in spotted drum, Nibea diacanthus. (28th August 2020) - Rong, Hua; Lin, Fan; Limbu, Samwel Mchele; Lin, Zhideng; Bi, Baoliang; Dou, Tengfei; Zhao, Lei; Wen, Xiaobo
Abstract: Swim bladder is an ideal source of collagen production in fish for improved human health. Proline (Pro) is the main proteinogenic amino acid needed for collagen production. However, the effects of Pro supplementation on the swim bladder collagen synthesis have rarely been evaluated in fish. We determined the effects of dietary Pro supplementation on swim bladder collagen synthesis and its possible signalling pathway in spotted drum, Nibea diacanthus . A total of 450 N. diacanthus (100 ± 3.05 g) were randomly assigned into six treatments and fed with diets supplemented with different levels of Pro (0, 2.5, 5, 7.5, 10 and 12.5 g/kg of dry diet, hereafter P0, P1, P2, P3, P4 and P5, respectively) for 8 weeks. At the end, we evaluated collagen synthesis in swim bladder and the expression of genes related to TGF‐β/Smad pathway in the fish. Dietary Pro levels increased significantly the contents of crude protein, total collagen (TC) and the levels of some amino acids in swim bladder than the control diet ( p  < .05). The optimum amount of dietary Pro inclusion in diets for swim bladder collagen synthesis in N. diacanthus was 7.6 and 7.5 g/kg based on crude protein and TC in swim bladder, respectively. Dietary Pro levels increased significantly the proline 4‐hydroxylase ( P4H ) content in fish serum, swim bladder, muscle and liver tissues than control ( p  < .05). The relative expression of collagen type I alpha 1 ( COL1A1 ), alpha 2 ( COL1A2 ) and mothers against decapentaplegic homolog 2 ( Smad2 ) genes in liver and swim bladder initially increased significantly as the concentration of Pro and later decreased ( p  < .05). Similarly, the relative expression of transforming growth factor beta ( TGF‐β ), P4Ha2 and P4Ha3 genes in the swim bladder increased significantly as dietary Pro levels increased ( p  < .05). Using K ‐means clustering analysis, dietary proline partly promoted collagen accumulation in swim bladder through upregulation of Smad2 and TGF‐βRT genes. Taken together, Pro affected the collagen metabolism in swim bladder, probably by regulating the TGF‐β/Smad pathway, most likely via transient overexpression of Smad2 gene.